2018
DOI: 10.2478/emj-2018-0019
|View full text |Cite
|
Sign up to set email alerts
|

Relations between risk attitudes, culture and the endowment effect

Abstract: The main purpose of this research was to examine whether systematic cross-national differences existed in risk preferences. As a part of the survey, it was also tested how the subjects decided on behalf of their friends. Considering the type of risk-taking and the role of endowment plus relevant cultural backgrounds, the answerers were grouped, and each segment could be identified. Finally, this segmentation could be correlated with behaviour in risk decisions. Here, the Allais situation was used testing respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Brand value sources are analyzed in their traditional structure defined by Aaker-that is, (1) imageries; (2) attitudes; (3) attributes, and (4) benefits. The components of brand value sources are set in accordance with provided literature review and with relevance to so far identified specifics of psychographic profile of Slovak consumers [54].…”
Section: Methodological Backgroundmentioning
confidence: 99%
“…Brand value sources are analyzed in their traditional structure defined by Aaker-that is, (1) imageries; (2) attitudes; (3) attributes, and (4) benefits. The components of brand value sources are set in accordance with provided literature review and with relevance to so far identified specifics of psychographic profile of Slovak consumers [54].…”
Section: Methodological Backgroundmentioning
confidence: 99%
“…There is a lack of research exploring the impact of nationality and culture on attitudes towards financial risk, particularly within Europe (Kolnhofer‐Derecskei, 2018). The present paper has attempted to address this lacuna by comprehensively examining the factors that affect attitudes to financial risk across six European countries.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
“…Furthermore, it forms an integral part of a business, as risk is attached to every choice between various alternatives and final decisions. Almost every important economic decision involves some risk and uncertainty [1].…”
Section: Introductionmentioning
confidence: 99%